Capítulo 3: Compreendendo as narrativas (Phenomenology, Humanities and Sciences, 2025)
Davidson explains in a clear and engaging way, based on Husserl's phenomenology, how a researcher can understand narratives. He describes in a surprisingly simple and profound way how to bracket our own worldview in order to discover and empathically explain “the motivations at work in another person’s experience.” He states that “the only way to access and understand another person's experiences or behavior is through empathy” and describes the process of building empathetic bridges to reach an understanding of their experience.
Keywords: Phenomenology